Florida’s Vessel Title Registration System as a Source of Boat Locations and Characteristics: A Case Study in Lee and Manatee Counties - Robert Swett; Charles Sidman; Timothy Fik; Bill Sargent (EDIS)
This Summary Report is based on Florida Sea Grant Technical Paper 138 (TP-138) of the same title, Florida’s Vessel Title Registration System as a Source of Boat Locations and Characteristics: A Case Study in Lee and Manatee Counties, published July 2004.